Incidence and burden of illness at the Tokyo 2020 Paralympic Games held during the COVID-19 pandemic: a prospective cohort study of 66 045 athlete days - Derman, Wayne; Runciman, Phoebe; Eken, Maaike; Boer, Pieter-Henk; Blauwet, Cheri; Bogdos, Manos; Idrisova, Guzel; Jordaan, Esme; Kissick, James; LeVan, Philipe; Lexell, Jan; Mohammadi, Fariba; et al. (British Journal of Sports Medicine, 2022)
ObjectiveTo describe the incidence and burden of illness at the Tokyo 2020 Paralympic Games, which was organised with strict COVID-19 countermeasures.MethodsDaily illnesses were recorded via the web-based injury and illness surveillance system (teams with their own medical staff; n=81), and local polyclinic services (teams without their own medical staff; n=81). Illness proportion, incidence and burden were reported for all illnesses and in subgroups by sex, age, competition period, sports and physiological system.Results4403 athletes (1853 female and 2550 male) from 162 countries were monitored for the 15-day period of the Tokyo Paralympic Games (66 045 athlete days). The overall incidence of illnesses per 1000 athlete days was 4.2 (95% CI 3.8 to 4.8; 280 illnesses). The highest incidences were in wheelchair tennis (7.1), shooting (6.1) and the new sport of badminton (5.9). A higher incidence was observed in female compared with male athletes (5.1 vs 3.6; p=0.005), as well as during the precompetition versus competition period (7.0 vs 3.5; p<0.0001). Dermatological and respiratory illnesses had the highest incidence (1.1 and 0.8, respectively). Illness burden was 4.9 days per 1000 athlete days and 23% of illnesses resulted in time loss from training/competition>1 day.ConclusionThe incidence of illness at the Tokyo 2020 Paralympic Games was the lowest yet to be recorded in either the summer or winter Paralympic Games. Dermatological and respiratory illnesses were the most common, with the burden of respiratory illness being the highest, largely due to time loss associated with COVID-19 cases. Infection countermeasures appeared successful in reducing respiratory and overall illness, suggesting implementation in future Paralympic Games may mitigate illness risk.